Adsorption of Aromatics on Silica Gel - K. -P. Roethe; R. Gutsche; W. Richter; A. Roethe; J. Caro; J. Kärger (Adsorption Science & Technology, 1986)
Breakthrough curves of naphthalene from n -alkane solution with specific feeds typical of liquid phase processes in packed beds of silica gel which contains pores larger than the critical diameter of the naphthalene molecule are investigated. With measurements under conditions of the linear region of the adsorption isotherm it is found that the observed mass-transport is mainly determined by the mixing process in the flowing bulk phase and by mass transfer through the boundary layer at the interface between the liquid bulk phase and the adsorbent grain. In comparison with these mechanisms, the influence of molecular transport processes in the pore system of the silica gel grain is negligibly small. This information is shown to be available by a direct observation of the elementary steps of molecular transport applying the n.m.r. pulsed field gradient technique.